Influence of a preschool preventive dental programme on caries prevalence, oral care and secretory immunity to Streptococcus mutans in young adults. Issue 2 (6th October 2017) - Aida, KL; de Paula Ramos, S; Seixas, GF; Bozza, A; Couto de Almeida, RS; Dezan Garbelini, CC
Abstract: Objective: To evaluate oral hygiene habits, decayed, missing and filled teeth (DMFT) and surfaces (DMFS), dental care, dietetic habits and anti‐ Streptococcus mutans salivary secretory Immunoglobulin A (SIgA) in young adults who attended a preventive programme during preschool age. Material and methods: The study group (Baby Clinic) comprised 72 patients, aged 18‐25 years, who had participated in the Baby Clinic preventive programme. The control group was age‐ and gender‐matched. The patients were examined and unstimulated whole saliva was sampled for detection of anti‐ S. mutans SIgA antibodies. Results: Control patients presented increased DMFS scores ( P  <   .05). Hygiene habits, cariogenic diet and antibody levels were not different between groups ( P  >   .05). Baby Clinic patients presented better periodontal status ( P  <   .005), less calculus ( P  <   .005) and bleeding on probing ( P  <   .005), and reported visiting dental services more regularly ( P  <   .05). Adjusted multivariate linear regression analysis demonstrated that DMFT was associated with study group ( P  <   .05), gender ( P  <   .05), parents' education ( P  <   .05), carbohydrate intake ( P  <   .001) and levels of anti‐ S. mutans SIgA ( P  <   .007). DMFS was associated with time elapsed since the last visit to the dentist ( P  <   .005) and weekly carbohydrate intake ( P  <   .005). Conclusion: Preventive programmes for preschool children positively impact on DMFS and periodontal status in young adults, but have no long‐term effects on dietary or hygiene habits.